Research on the Application of AI Technologies in Computer Network Data Analysis - Ho Tsz Lok (Transactions on Computer Science and Intelligent Systems Research, 2024)
In recent years, with the development of the Internet of Things and smart devices, the Future Internet project has driven innovation in network architecture by combining different models and resources. To manage complexity, creating abstract models has become a critical step in the field of computer networks. This study explores the application of AI techniques in network data analysis, demonstrating the possibilities of AI for real-time monitoring, anomaly detection, and the future development of AI. Despite the promising applications of AI technology, challenges such as privacy protection and dealing with cyber threats still need to be overcome. Future research should develop safer and more flexible AI algorithms to adapt to complex network environments.